PENGARUH DISIPLIN KERJA, KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PULP PT.RIAU PULP PANGKALAN KERINCI PELALAWAN RIAU - Sasmita, Jumiati (Jurnal Tepak Manajemen Bisnis, 2015)
The success of a company is certainly mostly dominat of the results performance of employees in work units operate. Object of this research is employees of pulp production at PT. Riau Riau Pulp Pangkalan Kerinci Pelalawan. The purpose of this research is to determine and analyze the effect of work discipline, leadership and motivation on the employeeâs performance..The numbering of research population is 92 peoples, While the sample used non staff employees totally is 78 peoples. Method of data collection using the questionnaire, where is ordinal data converted to interval data with using method of successive interval (MSI).The hypothesis research use multiple regression analysis with Y = 11,003 â 0,168X1 + 0,3342X2 + 0,204X3. Test results of coefficient determination (R2) is 30.3%, which gives sense that the contribution of 30.3% given by the variable work discipline, leadership and motivation to employees performance. The analysis showed that work discipline, leadership and motivation simultaneously had a significant effect and positive impact to emplyoyees performance. Leadership is given contribute the mostly in this tesis with value is 47,7%.Keywords : work discipline, leadership, motivation and employee performance